Classroom Communication in Early Childhood Education - Gita Swari, Sarasvati; Tantra, Dewa Komang; Pratiwi, Ni Putu Astiti (Journal of Education Reseach and Evaluation, 2020)
This study aims to investigated the speech act types and communication strategies in early childhood education. This research was a classroom research. Data were collected through unobtrusive observation during learning interactions. The obtained data were analyzed qualitatively. The recorded children’s and teachers’ speech acts were totaled 360. The research findings are as follows. Firstly, the recorded speech consisted of four types, they are: directive, expressive, declarative, and assertive acts. Directive acts were the most frequently used (93.3%), followed by expressive acts (5%), assertive acts (1.4%), and declarative acts (0.3%). The telling speech acts dominated the verbal interactions (44.4%) followed by request speech acts (32.2%). Secondly, 360 communication strategies were found. The telling and request sub-speech acts were delivered using compensatory strategies (96.11%). The teachers used 280 code-switching strategies (77.78%) while the children used none (0%); 14 non-linguistic forms strategies (3.89%) were used by the teachers while 6 self-repairs strategies (1.67%) by the children; 14 all-purpose words strategies (3.89%) were used by the teachers while none (0%) by the children; 14 asking for repetitions strategies (3.89%) were used by the teachers while none (0%) by the children; none filters/hesitation devices strategy (0%) was used by the teachers while 8 (2.22%) by the children; none (0%) literal translation strategy was used by the teachers while 12 (3.33%) by the children.  The most frequently directive acts imply towards the effectiveness of the children’s communicative skill.